Generalized unitarity at work: First NLO QCD results for hadronic S - Ellis, R; Melnikov, K; Zanderighi, G (2009)
We compute the leading color, next-to-leading order QCD corrections to the dominant partonic channels for the production of a W boson in association with three jets at the Tevatron and the LHC. This is the first application of generalized unitarity for realistic one-loop calculations. The method performs well in this non-trivial test and offers great promise for the future. © SISSA 2009.